ANALISA KUAT GESER BALOK BETON BERTULANG BERLAPIS BETON NORMAL-BETON STYROFOAM - Kusnadi Kusnadi; Imran Imran; Muhammad Rizal (Fakultas Teknik Universitas Khairun, 2022)
This study aims to analyze the shear strength of layered reinforced concrete beams as a composite. Concrete beams consist of normal concrete f'c 25 MPa on the compression side and lightweight concrete of 2.55 MPa, 1.32 MPa and 0.31 MPa on the tensile side as a consequence of the use of styrofoam as much as 30%, 40% and 50% of the concrete volume. This layered concrete beam is intended to reduce the weight of the structure. The tested beam is designed without shear reinforcement with dimensions of .150 cm long, 15 cm wide and 32 cm high, given 3Æ12 flexural reinforcement. The beam test used two concentrated loads with an effective shear-span ratio (a/d) 1.43 to ensure shear failure. The shear strength of layered concrete beams depends on the quality of each layer of concrete where the higher the quality of the cross-sectional concrete, the higher the shear strength. The prediction of shear strength based on the regulation is in line with the shear strength in the first oblique crack condition.